Enrollment Statistics & Demographics : Spring 2010 - UCO Office of Institutional Research (My University, 2010)
NOTICE TO DATA USERS: Broncho Analytics (https://bronchoanalytics.uco.edu) provides data users with the most current institutional data available from the Office of Institutional Research. These data reflect our efforts to correct for a number of data quality issues in the student information system & provide comparable time-series data. As we have transitioned to reporting from a data warehouse, our methods have evolved. Unfortunately, this might mean a report from many years ago is no longer comparable with data reported currently on Broncho Analytics. For example, past reports on student majors were based on the student’s “primary major” whereas current major reports are not limited in this way. Data users are encouraged to consult the Office of Institutional Research when comparing data from past editions of the Factbook and Demobook to current reports on Broncho Analytics.
Keywords: Demographic data; Universities and colleges. $2 fast $0 (OCoLC)fst01161597; Oklahoma. $2 fast $0 (OCoLC)fst01205031; Periodicals. $2 fast $0 (OCoLC)fst01411641; Statistics. $2 fast $0 (OCoLC)fst01423727